Determinan pembentuk karakter peserta didik pada kompetensi keahlian TITL di sekolah menengah kejuruan - Sikarti, Sikarti; Irwanto, Irwanto; Fakhurrohkhman, Muhammad (Directorate of Research and Community Service, Universitas Negeri Yogyakarta, 2024)
This study aims to obtain in-depth information about the determinants of the character formation process of students on the competence of Electrical Power Installation Engineering expertise in Vocational High Schools. The type of research used is qualitative with a case study method at SMKN 1 Padarincang. Data collection techniques used in this study were participatory observation, in-depth interviews, and documentation. Data analysis techniques using interactive models Miles and Huberman help ATLAS TI 9 software. The results obtained in this study are (1) The process of forming the character of students in the competence of Electrical Power Installation Engineering expertise, which is integrated with learning, habituation, extracurricular, and school management (2). Supporting factors for the process of forming the character of students include teachers with character, community, willingness of students, schools, and families. (3). Factors inhibiting the process of forming the character of students are less active teachers, school environment, students' desires, families, and inadequate infrastructure.